A globally relevant stock of soil nitrogen in the Yedoma permafrost domain - Strauss, Jens; Biasi, Christina; Sanders, Tina; Abbott, Benjamin W.; von Deimling, Thomas Schneider; Voigt, Carolina; Winkel, Matthias; Marushchak, Maija E.; Kou, Dan; Fuchs, Matthias; Horn, Marcus A.; Jongejans, Loeka L.; et al. (Nature communications, 2022)
Nitrogen regulates multiple aspects of the permafrost climate feedback, including plant growth, organic matter decomposition, and the production of the potent greenhouse gas nitrous oxide. Despite its importance, current estimates of permafrost nitrogen are highly uncertain. Here, we compiled a dataset of >2000 samples to quantify nitrogen stocks in the Yedoma domain, a region with organic-rich permafrost that contains ~25% of all permafrost carbon. We estimate that the Yedoma domain contains 41.2 gigatons of nitrogen down to ~20 metre for the deepest unit, which increases the previous estimate for the entire permafrost zone by ~46%. Approximately 90% of this nitrogen (37 gigatons) is stored in permafrost and therefore currently immobile and frozen. Here, we show that of this amount, ¾ is stored >3 metre depth, but if partially mobilised by thaw, this large nitrogen pool could have continental-scale consequences for soil and aquatic biogeochemistry and global-scale consequences for the permafrost feedback. A climate sensitive permafrost region (Yedoma domain) was found to contain globally relevant N stock of >40 Gt nitrogen, of which 4 to 16 Gt of the N could become available by thaw until 2100. This study increases the current estimates by nearly 50%.